PD-1/PD-L1 inhibitors for advanced or metastatic cervical cancer: From bench to bed - Huang, Weijia; Liu, Jiewei; Xu, Kai; Chen, Huilin; Bian, Ce (Frontiers in Oncology, 2022)
Advanced or metastatic cervical cancer has a poor prognosis, and the 5-year overall survival is <5% with conventional radiotherapy and chemotherapy. Immunotherapy, particularly immune checkpoint inhibitors (ICIs), achieved initial success in advanced solid tumors, while their efficacy and safety in advanced or metastatic cervical cancer remains to be explored. Previous studies found high-risk HPV infection and elevated PD-L1 expression in cervical precancerous lesions and squamous cell carcinoma. Meanwhile, elevated PD-L1 expression, high cytotoxic T lymphocyte infiltration, and abnormal cytotoxic T lymphocyte function might benefit inflammation infiltration for ICIs in the tumor microenvironment. Patients with HPV infection, squamous cell carcinoma, advanced stage, large tumor size, poor differentiation, metastatic disease, history of multiple childbirth and abortion, or a previous history of receiving chemotherapy might be associated with positive PD-L1 expression. Although there is no correlation between PD-L1 expression and prognosis using conventional radiotherapy, patients with high PD-L1 expression have a poorer prognosis. Several clinical studies demonstrate preliminary safety and efficacy for PD-1/PD-L1 inhibitors, and the exploration of combination strategies such as immunotherapy combined with chemotherapy, radiotherapy, anti-angiogenesis therapy, or dual ICIs is ongoing. This paper systematically reviews PD-L1 expression patterns and their relationship with prognosis, along with reported and ongoing clinical trials of PD-1/PD-L1 inhibitors in cervical cancer to clarify the prospect of ICIs for cervical cancer from bench to bed.